Ministry of Trade and Industry Decree No. 567 of the year 2010 On Amending Certain Provisions Of Ministerial Decree No. 257 of the Year 2010 On The Conditions Concerning The Release Of The Chinese Commodities = وزارة التجارة والصناعة قرار رقم 567 لسنة 2010 بتعديل بعض أحكام القرار الوزارى رقم 257 لسنة 2010 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.